Rural-Urban Migration in Colombia - Schultz, T. Paul (The Review of Economics and Statistics, 1971)
T HIS study attempts to explore the causes of internal migration in Colombia. Migration rates are first estimated for various groups in the population to clarify who migrates and to where. A model of interregional migration is then set forth and estimated for a sample of Colombian municipalities, from which we can infer the responsiveness of migration to some economic, demographic and political developments in the rural and urban sectors of the society.